An antimicrobial protein of the Riptortus pedestris salivary gland was cleaved by a virulence factor of Serratia marcescens. (February 2017) - Lee, Dong Jung; Lee, Jun Beom; Jang, Ho Am; Ferrandon, Dominique; Lee, Bok Luel
Abstract: Recently, our group demonstrated that the bean bug, Riptortus pedestris, is a good experimental symbiosis model to study the molecular cross-talk between the host insect and the gut symbiont. The Burkholderia symbiont is orally acquired by host nymphs from the environment in every generation. However, it is still unclear how Riptortus specifically interacts with entomopathogens that are abundant in the environmental soil. In preliminary experiments, we observed that a potent entomopathogen, Serratia marcescens, can colonize the midgut of Riptortus insects and was recovered from the midgut when Serratia cells were orally administered, suggesting that this pathogenic bacterium can escape host immune defenses in the salivary fluid. We examined how orally fed Serratia cells can survive in the presence of antimicrobial substances of the Riptortus salivary fluid. In this study, a 15 kDa trialysin-like protein from the salivary gland of R. pedestris and a potent virulence factor of Serratia cells, a serralysin metalloprotease, from the culture medium of S. marcescens were successfully purified to homogeneity. When the purified Riptortus trialysin (rip-trialysin) was incubated with purified serralysin, rip-trialysin was specifically hydrolyzed by serralysin, leading to the loss of antimicrobial activity. These results clearly demonstrated that a potent virulent metalloprotease of S. marcescens functions as a key player in the escape from the salivary fluid-mediated host immune response, resulting in successful colonization of S. marcescens in the host midgut. Highlights: Salivary glands of insects contain some antimicrobial substances to protect the host. Two proteins, host antimicrobial peptides and pathogen virulence factor were purified. Antimicrobial peptides were specifically hydrolyzed by virulence factor. virulent factor can escape from the salivary fluid-mediated host immune response.